Ciliary functional analysis: Beating a path towards standardization. Issue 10 (16th July 2019) - Kempeneers, Céline; Seaton, Claire; Garcia Espinosa, Bernardo; Chilvers, Mark A.
Abstract: Primary ciliary dyskinesia is an inherited disorder in which respiratory cilia are stationary, or beat in a slow or dyskinetic manner, leading to impaired mucociliary clearance and significant sinopulmonary disease. One diagnostic test is ciliary functional analysis using digital high‐speed video microscopy (DHSV), which allows real‐time analysis of complete ciliary function, comprising ciliary beat frequency (CBF) and ciliary beat pattern (CBP). However, DHSV lacks standardization. In this paper, the current knowledge of DHSV ciliary functional analysis is presented, and recommendations given for a standardized protocol for ciliary sample collection and processing. A proposal is presented for a quantitative and qualitative CBP evaluation system, to be used to develop international consensus agreement, and future DHSV research areas are identified.